Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

For differential equation (1-e^x)sec^2ydy+3e^xtanydx=0 If y(ln2)=pi/4 Then y(ln3) is equal to

For differential equation 
(1-e^x)sec^2ydy+3e^xtanydx=0
If y(ln2)=pi/4
Then y(ln3) is equal to

Grade:12

1 Answers

Aditya Gupta
2080 Points
2 years ago
first of all put tany=z which means dz=sec^2ydy so the eqn becomes
(1-e^x)dz/dx+3ze^x=0
or dz/z= 3e^xdx/(e^x – 1)
integrate both sides and plug in the initial conditions.
lnz+C=3ln(e^x – 1) 
you can calculate the final answer now

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free